2018
DOI: 10.1371/journal.pone.0204272
|View full text |Cite
|
Sign up to set email alerts
|

Proprietary management and higher readmission rates: A correlation

Abstract: IntroductionReducing preventable readmissions among Medicare beneficiaries is an effective way to not only reduce the exorbitantly rising cost in healthcare but also as a measure to improve the quality of patient care. Many of the previous efforts in reducing readmission rate of patients have not been very successful because of ill-defined quality measures, improper data collection methods and lack of effective strategies based on data driven solutions.MethodsIn this study, we analyzed the readmission data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The studies included numbers of patients ranging from 122 to 524,892 for THA, from 84 to 952,593 for TKA, and from 1596 to 878,098 for THA and TKA combined. Four studies did not report the number of patients included (15,27,28,29). A wide range was found for the number of hospitals included for THA, TKA, and THA and TKA combined (i.e.…”
Section: Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included numbers of patients ranging from 122 to 524,892 for THA, from 84 to 952,593 for TKA, and from 1596 to 878,098 for THA and TKA combined. Four studies did not report the number of patients included (15,27,28,29). A wide range was found for the number of hospitals included for THA, TKA, and THA and TKA combined (i.e.…”
Section: Characteristicsmentioning
confidence: 99%
“…From the 13 studies reporting readmission rates, the between-hospital variation was reported in 5 studies (3 MQ, 2 LQ) for THA (9,21,30,35,36), 4 studies (3 MQ, 1 LQ) for TKA (21,33,35,37), and 6 studies (3 MQ, 3 LQ) for THA and TKA combined (15,16,28,38,39,40). Ten studies reported the variation for readmission more than once with different indicator definitions in all domains except for the type of patients selected (Table 4).…”
Section: Readmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…All multivariable models controlled for important hospitallevel characteristics (see the Appendix for covariate details). These include hospital location 18 , geographic region 19 , hospital size (number of beds) 20 , medical school affiliation 20 , and ownership 21 . We also controlled for the volume of total hip and knee replacements that qualified for the measures 22 , the Disproportionate Patient Percentage 23 , and the transfer-adjusted case mix 24 , all of which were specified as continuous variables.…”
Section: Covariatesmentioning
confidence: 99%